2017
DOI: 10.1071/rd16320
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormones interact with natriuretic peptide C to delay nuclear maturation, to maintain oocyte–cumulus communication and to improve the quality of in vitro-produced embryos in cattle

Abstract: In vivo, oocyte maturation is triggered by the ovulatory LH surge, whereas in vitro it is precociously induced when the cumulus-oocyte complex is removed from the follicle. Natriuretic peptide C (NPPC) delays germinal vesicle breakdown (GVBD) while increasing oocyte-cumulus communication during in vitro maturation (IVM) in cattle. In the present study we first tested the hypothesis that steroids secreted by the follicle (17β-oestradiol, progesterone and androstenedione) interact with NPPC to delay GVBD and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 41 publications
0
27
0
5
Order By: Relevance
“…Cumulus cell-derived cGMP inhibits the reduction of cAMP concentration by the inhibition of PDE3A, an oocyte-specific phosphodiesterase, which is a trigger for meiotic resumption [78]. As with mice, bovine cumulus cells express NPR2 mRNA [65,68,79] and protein [68], and meiotic resumption of oocytes can be arrested during culture of cumulus-oocyte complexes (COCs) with NPPC [65,67,68,70,80]. Although NPR2 was not expressed in oocytes in mice [68], some studies reported the expression of NPR2 mRNA [68,79] and protein [68] in bovine oocyte membranes, and meiotic resumption of denuded oocytes was arrested by NPPC [68].…”
Section: Culturing Oocyte With Natriuretic Peptide Precursor Type Cmentioning
confidence: 99%
“…Cumulus cell-derived cGMP inhibits the reduction of cAMP concentration by the inhibition of PDE3A, an oocyte-specific phosphodiesterase, which is a trigger for meiotic resumption [78]. As with mice, bovine cumulus cells express NPR2 mRNA [65,68,79] and protein [68], and meiotic resumption of oocytes can be arrested during culture of cumulus-oocyte complexes (COCs) with NPPC [65,67,68,70,80]. Although NPR2 was not expressed in oocytes in mice [68], some studies reported the expression of NPR2 mRNA [68,79] and protein [68] in bovine oocyte membranes, and meiotic resumption of denuded oocytes was arrested by NPPC [68].…”
Section: Culturing Oocyte With Natriuretic Peptide Precursor Type Cmentioning
confidence: 99%
“…However, in most of the above cited cases the reported results showed only a slight improvement in developmental competence depending on the approach used. Often, rather than increasing the number of blastocysts obtained, an improvement in the parameters related to embryo quality was observed (Luciano et al, 2011;Dieci et al, 2013Dieci et al, , 2016Lodde et al, 2013;Rose et al, 2013;Franciosi et al, 2014;Zeng et al, 2014;Azari-Dolatabad et al, 2016;Li et al, 2016;Park et al, 2016;Sanchez et al, 2017;Soares et al, 2017). For instance, blastocysts with higher number of cells or embryo with better developmental kinetics.…”
Section: Controlling Campmentioning
confidence: 99%
“…However, studies using microsurgical removal of the oocyte from the COC and co-culture of oocytectomized COCs with secreting denuded oocytes indicate that OSF are needed for cumulus expansion in mice, but not in cattle, pigs or rats (Buccione et al, 1990;Ralph et al, 1995;Vanderhyden et al, 2003). More recently, the same approach demonstrated that OSF also play a central role in the regulation of glycolytic activity of cumulus cells in mice (Sugiura et al, 2005), whereas in cattle, utilization 602…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the enhanced effects on nuclear maturation and gap junction functionality were interpreted as a consequence of greater NPPC signaling and cGMP production in the presence of steroids. Moreover, the combination of NPPC with follicular steroids in a pre-IVM culture promoted improved embryo quality (assessed by total cell number), suggesting that this strategy may be useful to improve IVM/IVF outcomes (Soares et al, 2017).…”
Section: Oocyte and Cumulus-derived Factors In The Regulation Of Nuclmentioning
confidence: 99%